Quinazolines and anticancer activity: A current perspectives. Issue 5 (4th March 2017) - Rahman, Mujeeb Ur; Jeyabalan, G.; Saraswat, Pankaj; Parveen, Gazala; Khan, Shahroz; Yar, M. Shahar
ABSTRACT: Cytotoxicity and genotoxicity of anticancer drugs to the normal cells are major problems in cancer therapy and endanger the risk of inducing secondary malignancy. Current regimen with anticancer drugs produces various toxicities. Therefore, there is urgent need for the development of newer and safer drugs. Quinazoline derivatives occupy a pivotal position in modern medicinal chemistry and have found applications as medicines. Various researches have been performed on quinazoline and their derivatives for anticancer activity and pharmacological importance of this scaffold has been well established. Quinazoline reported to possess a number of biological activities. It has multiple pharmacophores, which bring together knowledge of a target with understanding of the molecule types that might interact with the target family. The current review focuses on biological actions done for various targets along with the brief description of the targets which may facilitate the development of more potent and effective anticancer agents. GRAPHICAL ABSTRACT: